Rapid removal of chloramphenicol via the synergy of Geobacter and metal oxide nanoparticles. (January 2022) - Xiao, Leilei; Liu, Fanghua; Kumar, P. Senthil; Wei, Yunwei; Liu, Jian; Han, Dianfeng; Shan, Shangjie; Wang, Xingyu; Dang, Run; Yu, Jiafeng
Abstract: The wide use of chloramphenicol and its residues in the environments are an increasing threat to human beings. Electroactive microorganisms were proven with the ability of biodegradation of chloramphenicol, but the removal rate and efficiency need to be improved. In this study, a model electricigens, Geobacter metallireducens, was supplied with and Fe3 O4 and MnO2 nanoparticles. Five times higher chloramphenicol removal rate (0.71 d −1 ) and two times higher chloramphenicol removal efficiency (100%) was achieved. Fe3 O4 and MnO2 nanoparticles highly increased the current density and NADH-quinone oxidoreductase expression. Fe3 O4 nanoparticles enhanced the expression of alcohol dehydrogenase and c-type cytochrome, while MnO2 nanoparticles increased the transcription of pyruvate dehydrogenase and Type IV pili assembly genes. Chloramphenicol was reduced to a type of dichlorination reducing product named CPD3 which is a benzene ring containing compound. Collectively, Fe3 O4 and MnO2 nanoparticles increased the chloramphenicol removal capacity in MFCs by enhancing electron transfer efficiency. This study provides new enhancing strategies for the bioremediation of chloramphenicol in the environments. Graphical abstract: Image 1 Highlights: Fe3 O4 and MnO2 particles showed five times increase in chloramphenicol removal rate. Transcriptomic showed an increase of NADH-quinone oxidoreductase in two treatments. Fe3 O4 and MnO2 nanoparticles increased electron transfer efficiency. The primary enzymes for chloramphenicol reduction were different in three treatments.